PTEN: Tumor Suppressor and Metabolic Regulator - Chen, Chien-Yu; Chen, Jingyu; He, Lina; Stiles, Bangyan L. (Frontiers in Endocrinology, 2018)
Phosphatase and Tensin Homologue deleted on Chromosome 10 (PTEN) is a dual phosphatase with both protein and lipid phosphatase activities. PTEN was first discovered as a tumor suppressor with growth and survival regulatory functions. In recent years, the function of PTEN as a metabolic regulator has attracted significant attention. As the lipid phosphatase that dephosphorylates phosphatidylinositol-3, 4, 5-phosphate (PIP3), PTEN reduces the level of PIP3, a critical 2nd messenger mediating the signal of not only growth factors but also insulin. In this review, we introduced the discovery of PTEN, the PTEN-regulated canonical and nuclear signals, and PTEN regulation. We then focused on the role of PTEN and PTEN-regulated signals in metabolic regulation. This included the role of PTEN in glycolysis, gluconeogenesis, glycogen synthesis, lipid metabolism as well as mitochondrial metabolism. We also included how PTEN and PTEN regulated metabolic functions may act paradoxically towards insulin sensitivity and tumor metabolism and growth. Further understanding of how PTEN regulates metabolism and how such regulations lead to different biological outcomes is necessary for interventions targeting at the PTEN-regulated signals in either cancer or diabetes treatment.